Metallic magnetic calorimeter arrays for the first phase of the ECHo experiment - Mantegazzini, Federica; Barth, Arnulf; Dorrer, H.; Düllmann, Ch. E.; Enss, Christian; Fleischmann, Andreas; Hammann, Robert; Kempf, Sebastian; Kieck, T.; Kovac, N.; Velte, Clemens; Wegner, Mathias; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2022)
The ECHo experiment has been designed for the determination of the effective electron neutrino mass by means of the analysis of the end-point region of the 163Ho electron capture spectrum. Metallic magnetic calorimeters enclosing 163Ho are used for the high energy resolution calorimetric measurement of the 163Ho spectrum. For the first phase of the experiment, ECHo-1k, a 72-pixel MMC array has been developed. The single-pixel design has been optimised to reach 100% stopping power for the radiation emitted in the 163Ho electron capture process (besides the electron neutrino) and an energy resolution ΔEFWHM<10eV. We describe the design of the ECHo-1k detector chip, the fabrication steps and the characterisation at room temperature, at 4 K and at the final operation temperatures. In particular, a detailed analysis of the results from these tests allowed to define a quality check protocol based on parameters measurable at room temperature. We discuss the performance achieved with the two ECHo-1k detector chips - the first one with 163Ho implanted in gold and the second one with 163Ho implanted in silver - which have been used for the high statistics measurement of the ECHo-1k experiment. An average activity per pixel of 0.81Bq and 0.71Bq and an average energy resolution of 6.07eV FWHM and 5.55eV FWHM have been achieved with these two detectors, fulfilling the requirements for the first phase of the ECHo experiment.